PENGARUH PERIKLANAN TERHADAP KEPUTUSAN KONSUMEN (PENDERITA HIPERTENSI DAN KELUARGA PENDERITA HIPERTENSI) MEMILIH PENGOBATAN HERBAL - Debby Yulianthi Maria; Bety Agustina Rahayu; Novika Candra Astuti (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: The problem of hypertension is a frequent topic of discussion. Hypertension is classified as the silent killer. People have been good at choosing how to maintain their health in which advertising is one of the factors that influence them choose health products. Behavioral treatment itself is mostly done by the community so that it can lead to medication errors.  Objective: This study is expected to determine the effect of advertising on consumer decision (hypertensive and hypertensive family) chose herbal medicine (a case study in Padukuhan, Pungkuran Pleret, Bantul, District of Yogyakarta) using theory of AIDA model. This study used Cross Sectional Research. Methode: The samples in this study are patients with hypertension and families who have family members living in hypertensive patients in Padukuhan Pungkuran with the number of respondents is 432 people, the sampling method used is total sampling. Techniques and instruments of data collection used library research and field research by means of interviews and questionnaires. Processing of data by multiple linear regression analysis, coefficient of determination (R2) with the results of buying interest is affected by variable interest and action. Result: Based on the data processing, F score is 19 503, only the factor of interest and action that together influential significantly on consumer buying interest towards herbal products. The most influence on consumer purchase interest is variable action, judging from the results of the t-value (4.609) or regression coefficient (0.197).